Analysis of Physical Layer Impairments Resources Allocation Aware Algorithm/Framework in Transparent OTNs - Nleya, Bakhe; Molefe, M; Khulekani, Sibiya (2024 International Conference on Electrical, Computer and Energy Technologies (ICECET, 2024)
Present-day, limitedly fixed wavelength routed based all Transparent Optical Transport Networks (OTNs) are quite energy efficient in comparison to translucent and opaque equivalents. As a result they are also regarded as a practical solution transport network provisioning ultrahigh bandwidth capabilities to support the various applications and services. The resulting heterogeneous nature of present-day global traffic makes such wavelength-routed networks spectrally inefficient. However, advancements in DSP techniques, modulation approaches, and transmission impairment mitigation techniques have vastly improved such net-works' spectral efficiencies and optical reach. The paper thus reviews the efficiency in the operation of an orthogonal frequency division multiplexing (OFDM) based Transparent OTN that is characterized by flexibility in the provisioning of available spectral resources. We address the challenges of optimal routing level allocation of wavelengths subject to maximizing spectral efficiencies. In so doing, we also consider the impact of various physical impairments. We introduce a quality factor-based tool (Q-factor) that aids in choosing op-timal routes. Ultimately, The tool is later incorporated into a proposed resource allocation framework's algorithms, which focus on ensuring spectral efficiency and overall network energy-efficient operation. Overall, we conclude that the pro-posed transport network architecture is relatively efficient regarding energy and spectral efficiencies.